Triptriolide Alleviates Lipopolysaccharide-Induced Liver Injury by Nrf2 and NF-κB Signaling Pathways - Yang, Yi-Qi; Yan, Xiao-Teng; Wang, Kai; Tian, Rui-Min; Lu, Zhao-Yu; Wu, Li-Lan; Xu, Hong-Tao; Wu, Yun-Shan; Liu, Xu-Sheng; Mao, Wei; Xu, Peng; Liu, Bo (Frontiers in Pharmacology, 2018)
Nrf2 (Nuclear Factor Erythroid 2 Related Factor 2) transcription factor not only regulates oxidative stress response, but also represses inflammation by regulating cytokines production and cross-talking with NF-κB signaling pathways. Nrf2 plays an essential role in liver injury induced by oxidative stress and inflammation. Triptriolide (T11) is a minor component of Tripterygium wilfordii Hook F. (TwHF), which can be obtained by hydrolysis reaction of triptolide (T9). The major purpose of this study is to clarify the regulating effects of T11 on oxidative stress and inflammation in vivo and in vitro. LPS-stimulated RAW 264.7 cells were used to verify the regulating effects of T11 on oxidative stress (ROS and Nrf2 signaling pathway) and inflammatory cytokines production (TNF-α, IL-6 and IL-1β). The antioxidant responsive element (ARE) luciferase assay was employed to evaluate Nrf2 activation effect of T11 in HEK-293T cells. The acute liver injury (ALI) model was induced by Lipopolysaccharides (LPS) in BALB/c mice, which were used to explore the protective effects (ALT, AST, MDA, SOD, histopathology and neutrophils/ macrophages filtration) and the underlying mechanisms (Nrf2 and NF-κB signaling pathway) of T11 on ALI model. Firstly, the results showed that T11 can not only effectively decrease the productions of inflammatory cytokines (TNF-α, IL-6 and IL-1β), ROS and NO in LPS-stimulated RAW 264.7 cells, but also further significantly increase the activity of Nrf2 in HEK-293T cells. Secondly, the results suggested that T11 could dramatically decrease the oxidative stress responses (SOD and MDA) and inflammation (histopathology, neutrophils/macrophages filtration, TNF-α, IL-6 and IL-1β production) in LPS-induced ALI in BALB/c mice. Finally, the results implied that T11 could dramatically increase Nrf2 protein expression and decrease p-TAK1, p-IκBα and NF-κB protein expression both in vivo and in vitro. In conclusion, our findings indicated that T11 could alleviate LPS induced oxidative stress and inflammation by regulating Nrf2 and NF-κB signaling pathways in vitro and in vivo, which offers a novel insights for the application of TwHF in clinical.